Pelatihan Aplikasi Mendeley Terhadap Tingkat Pengetahuan Mahasiswi STIKES Graha Edukasi - Nurhikmah; Nur Aliya Arsyad; Muliyana; Reskiawati Azis (Cv. Utility Project Solution, 2023)
In the current digital era, the Mendeley application has become one of the popular and useful tools for organizing, storing, and sharing references and research sources. However, despite Mendeley's wide recognition, not all midwifery students are aware of its full potential. Some students may lack sufficient understanding of Mendeley's features or may not be familiar with using the application in an academic context. As a result, they may not be able to fully utilize Mendeley to enhance the efficiency and quality of their scientific writing. The methods used in this training were lectures and discussions. The Community Service activity was conducted in March 2023, specifically at the Graha Edukasi Makassar STIKES campus. The participants consisted of 30 midwifery students. The results of the activity after providing training on the Mendeley application showed that the majority of the students (97%) demonstrated an increased level of knowledge regarding the Mendeley application. Mendeley can improve the knowledge level of the students, which is expected to have a positive implication for STIKES Graha Edukasi Makassar in enhancing the quality of education in the field of midwifery. Through Mendeley application training, this institution can support midwifery students in developing relevant digital skills and information literacy aligned with the needs of the times. Therefore, it is expected that this training can serve as a foundation for the development of broader training activities in the field of information technology and communication